Improvement of force history pattern in composite tubular structures by developed trigger mechanisms - de la Cuesta, J. J.; Ghasemnejad, Hessam (Springer, 2022)
This paper investigates the effect of various trigger mechanisms on the force history pattern, initial collapse load, mean force and specific energy absorption of CFRP composite tubular absorbers. These trigger mechanisms are bevel with angles of 15°, 30°, 45° and 60° and tulip with angles of 60° and 90° and tip numbers of 4 and 6. Experimental studies were performed for three trigger mechanisms of Bevel (B30° and B60°) and tulip with four tips and angle of 60°, 4T60. It was shown that tulip mechanisms significantly change the force–displacement pattern in comparison with bevel triggers. In this case, the initial collapse load decreases, which leads to improving the crush force efficiency (CFE) and progressive energy absorption. This analysis also contains numerical modelling, which investigates other designs of bevel and tulip trigger mechanisms with different angles. Finally, numerical results are validated against experimental results using advanced finite element techniques in LS-Dyna. The developed tulip trigger mechanisms indicated a significant change of crushing force history, which results in improvement of crashworthiness parameters.
Keywords: Trigger; CFRP; Tulip; Force Pattern; Absorbed Energy